THE ABUNDANCE OF HELIUM AND STELLAR PULSATION - Kovtyukh, V. V. (Одеські астрономічні публікації, 2017)
Radial gradient of relative amplitude of the light variation FV for galactic classical Cepheids is found. The gradient has different signs for two cases: P > 8d and P < 8d. For P > 8d the gradient is negative. This gradient is caused by gradient of helium content in the primordial clouds, where Cepheids were born. In agreement with theoretical calculations, the amplitude increase with an increasing of the helium content. For this dependence the following calibration was obtained: [He/H] = (FV - 0.54) dex Y= 0.55FV - 0.03 In case P < 8d the amplitude (and also asymmetry parameter M-m) is mainly affected by metallicity.